TEACHING CORRECT PRONUNCIATION OF LATIN AS AN INTERNATIONAL LANGUAGE OF MEDICINE IN MEDICAL EDUCATION INSTITUTIONS (Archive of Conferences, 2022)
In this article, the author aims to describe the difficulties in teaching correct pronunciation in Latin, which is used in general practice as an international medical language: problems, causes and solutions faced by teachers and students. As Latin is a foreign language for Uzbek students, pronunciation is being considered to prevent it from becoming a professional problem.